THE NEW COMPOSITE AND SPACE GRID CABLE-STAYED CONSTRUCTIONS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The new space structures are considered –space cable composite steel and concrete covering, consisting of ferrocement slabs and structural steel lattice. Their structure, features, advantages, scope and possible design solutions are described. Keywords:composite, space grid, cable-stayed, plate, lattice, a node.